Analisis Pengaruh Minimasi Pajak Dan Mekanisme Bonus Terhadap Transfer Pricing Dengan Komite Audit Sebagai Variabel Pemoderasi - Nehayati, Nela; Pamungkas, Imang Dapit; Ratnawati, Juli; Durya, Ngurah Pandji Mertha Agung (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This research aims to test and analyze the direct influence of tax minimization strategies, tunneling incentives, and bonus mechanisms on transfer pricing decisions. Meanwhile, the indirect influence involves the audit committee as a moderating factor, to test its influence on transfer pricing practices. The data used in this research comes from the Annual Reports of natural resource sector companies listed on the Indonesia Stock Exchange during the 2021-2022 period. A total of 185 companies used the purposive sampling method, producing a sample of 104 data which was analyzed using WarpPLS 8.0. Based on the research results, tax minimization has a direct influence on transfer pricing, while the bonus mechanism has no influence on transfer pricing and the audit committee cannot moderate the influence of both on transfer pricing. The implications of this research emphasize the importance of companies paying attention to their tax and transfer pricing policies as part of a general risk management and compliance strategy to prevent potential abuse or tax compliance risks.